The successful factors of heritage interior scheme for heritage museum : case study 'Rumah Teh Bunga' in George Town Penang / Norashikin Abdul Karim, Siti Norlizaiha Harun and Salwa Ayob - Abdul Karim, Norashikin; Harun, Siti Norlizaiha; Ayob, Salwa (2018)
There is a conflict between the conservation of museum heritage scheme and the building restoration, mainly because the idea of operating a museum in heritage building depends on restoration requirements. There is a lacking of practice to bring back the heritage interior scheme after conservation. Consequently, the history of historic building is the priority and it becomes the most expensive element of the collection.To achieve the successfull interior historic scheme for exhibition inside heritage building, there are some factors that should be considered.Thereare; space remain intact; space heritage value; heritage space interpretation; heritage space ambience; risk of exhibition fittings; exhibition space contents; and collection adaptation. This paper is part of an ongoing research aimed at revealing these 7 successful factors of interior heritage scheme at Malay Penang Gallery also called 'Rumah Teh Bunga' in George Town, Penang. Assessment evaluation technique in a form of rubrics were used to test these 7 successful factors. The finding of successful factors could be served as guidelines to manage the exhibition heritage scheme toset up museum or gallery inside heritage building. Indirectly, it will contribute ultimate goal to make visitors love history and love to come to museum.